Utilizing Lesson Study In Enhancing Teaching Pedagogy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Teacher’s pedagogy is a key factor in achieving better learning from both the teacher and the students through the application of theory and practice in teaching a particular subject and its context. In view of enhancing the teaching pedagogy of teachers, this paper sought to investigate the impact of Lesson Study (LS) in teaching pedagogy through the delivery of netiquette instruction – a topic that was  deemed very relevant to young adults in this Information Age. The process of LS revealed themes that pointed out how teaching pedagogy could be enhanced. In the light of the LS process, teachers’ collaboration in the preparation of lesson and conduct of classroom instruction revealed a significant ruminations on how lessons could be improved. In particular, the post-lesson debriefing revealed that the presence of integration of empathy in the conduct of instruction was a positive teaching practice. However, the need for the following concerns to further enhance teaching pedagogy through LS must be considered: a.) give emphasis on researching in detail the material to be taught; b.) capitalize on extracting students’ view and insights in searching for meaning; and c.) lead the students to abstractions. In view of these results, it is concluded that the teachers’ collaboration in the whole process of LS unmasked a significant impact on how the modifications and revisions of teaching strategies and approaches in the delivery of lessons could be done to enhance teaching pedagogy